Comparison of Serum HIF-1α Levels in Swimming Athletes Before and After Hypoxic Non-Hypoxic Exercise - Syahrastani Syahrastani; Argantos Argantos; Siska Alicia Farma (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
The situation of lack of oxygen supply to cells and tissues is often not realized by many people (hypoxia). Hypoxia can occur in various situations in life. The main effect of hypoxia is the effect on the brain, so the body will do everything it can to restore the state of homeostasis. HIF-1α protein is a marker of hypoxic conditions. HIF-1α regulates the synthesis of many genes to maintain and restore body homeostasis from hypoxia to normoxia. This study was a descriptive study with cross-sectional design. The sample of this study were six swimming athletes with a 12-19 year age range who met the inclusion and exclusion criteria. The HIF-1α protein is measured by the ELISA method. Data were analyzed statistically. The results showed higher levels of HIF-1α after anaerobic exercise than the levels of HIF-1α before and after aerobic exercise. This is greatly influenced by the intensity of the exercise carried out. This proves that cellular adaptation to hypoxia is more stable in aerobic exercise, where the body's metabolism during aerobic exercise is more stable